In the Neue Friedrichstrasse standing in the middle: Augustin Souchy; behind bars: Karl Potsler and Otto Hartwig
In the Neue Friedrichstrasse standing in the middle: Augustin Souchy; behind bars: Karl Potsler and Otto Hartwig.